STRATEGI PENGEMBANGAN PEMASARAN JAHE DI DESA MBOHANG KECAMATAN LELAK KABUPATEN MANGGARAI - Maria Alfira; Paulus Un; Yakobus C.W. Siubelan (Yayasan Panca Bakti Wiyata Pangandaran, 2026)
Ginger is one of the plantation commodities with high economic value and is widely used as raw material for food industries, health drinks, and traditional medicine. Mbohang Village, Lelak District, Manggarai Regency is one of the areas with significant potential for ginger commodity development. However, the ginger marketing system in the area still faces several obstacles, such as farmers’ dependence on collectors, limited market access, and fluctuating prices that affect farmers’ income stability. This study aims to analyze internal and external factors influencing ginger marketing development and formulate marketing development strategies based on IFAS, EFAS, and SOAR analyses. The research employed a descriptive quantitative method using purposive sampling. A total of 40 respondents consisting of 36 ginger farmers and 4 collectors participated in the study. Data collection techniques included interviews, observation, and documentation. The results showed that the main strengths consisted of good product quality, increasing production quantity, good relationships between farmers and traders, and extensive business experience. Major opportunities included stable market demand, loyal customers, and strategic location. The IE matrix analysis indicated that the business position was in Quadrant I, meaning growth and build strategy. Strategies generated through SOAR analysis included improving marketing promotion, expanding market access, increasing production quality and quantity, and strengthening cooperation among farmers, traders, and the government. These strategies are expected to improve ginger product competitiveness and enhance farmers’ welfare in Mbohang Village.